Enhancing the efficiency of a symmetric flat-plate solar collector via the use of rutile TiO2-water nanofluids. (August 2020) - Moravej, Mojtaba; Bozorg, Mehdi Vahabzadeh; Guan, Yu; Li, Larry K.B.; Doranehgard, Mohammad Hossein; Hong, Kun; Xiong, Qingang
Abstract: Flat-plate solar collectors are one of the cleanest and most efficient heating systems available. This experimental study explores the effect of replacing water with surfactant-free rutile TiO2 –water nanofluids as the working fluid in a symmetric flat-plate solar collector. The efficiency of the collector was investigated in Aghajari, a city in the south of Iran. Analysis was performed according to the ASHRAE standard, taking into account the flow rate of the heat transfer fluid (HTF), the solar irradiance, and the temperature difference between the inlet and outlet. Results show that the use of TiO2 –water nanofluids can improve thermal efficiency relative to water. As the solar irradiance or the HTF flow rate increases, the effect of nanoparticle addition on the collector efficiency gains becomes more pronounced. The maximum efficiency of the collector, when filled with a 1 wt% TiO2 -water nanofluid, is found to be approximately 78%; this represents maximum and average efficiency gains of 9.80% and 6.64%, respectively, relative to the water baseline. In addition, the maximum efficiency gains are 17.41%, 27.09%, and 33.54% for 1 wt%, 3 wt%, and 5 wt% nanoparticle concentration, respectively.